2019
DOI: 10.1002/tea.21584
|View full text |Cite
|
Sign up to set email alerts
|

Equity in college physics student learning: A critical quantitative intersectionality investigation

Abstract: We investigated the intersectional nature of race/racism and gender/sexism in broad scale inequities in physics student learning using a critical quantitative intersectionality. To provide transparency and create a nuanced picture of learning, we problematized the measurement of equity by using two competing operationalizations of equity: Equity of Individuality and Equality of Learning. These two models led to conflicting conclusions. The analyses used hierarchical linear models to examine student's conceptua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 68 publications
2
51
1
Order By: Relevance
“…This is supported by the instructors reporting using more studentcentered collaborative teaching techniques when their courses included LAs. These teaching techniques support greater conceptual learning than teacher-centered lecture [86,93,94]. Van Dusen and Nissen [86] found that collaborative instructional practices increased conceptual learning across all demographic groups but that it did not eliminate differences across demographic groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is supported by the instructors reporting using more studentcentered collaborative teaching techniques when their courses included LAs. These teaching techniques support greater conceptual learning than teacher-centered lecture [86,93,94]. Van Dusen and Nissen [86] found that collaborative instructional practices increased conceptual learning across all demographic groups but that it did not eliminate differences across demographic groups.…”
Section: Discussionmentioning
confidence: 99%
“…These teaching techniques support greater conceptual learning than teacher-centered lecture [86,93,94]. Van Dusen and Nissen [86] found that collaborative instructional practices increased conceptual learning across all demographic groups but that it did not eliminate differences across demographic groups. Greater conceptual learning in the LA-supported courses would have resulted in higher grades if the grading practices were similar between traditional and LA-supported courses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Critical Quantitative Intersectionality (CQI) provides a framework for applying critical theory [7,13,14] and intersectionality [15,16], which have been used primarily for qualitative studies [17,18], to quantitative studies in physics education [19]. CQI examines unique constellations of race, gender, and class social location as categories of experience in a given educational context [20].…”
Section: Frameworkmentioning
confidence: 99%